On interactions of frictional cracks (Archives of Mechanics - Test, 2000)
This paper deals with the estimation of the stress intensity factors for interacting Mode-II cracks undergoing frictional sliding under overall compressive stresses. Crack interaction effects are examined via the Kachanov method that is extended here to account for frictional and cohesive resistance on crack faces. The accuracy of the obtained results is verified through comparison with the "exact" numerical solutions obtained using a boundary element method.